(b+c-a/a)+(a+c-b/b)+(a+b-c/c)
=b/a +c/a -1+a/b+c/b-1 +a/c+b/c -1
=(b/a +a/b)+(c/a +a/c)+(c/b +b/c)-3≥ 2+2+2-3(均值不等式)
所以(b+c-a/a)+(a+c-b/b)+(a+b-c/c)≥ 3
证明:
∵列项可得
(b+c-a)/a=(b/a)+(c/a)-1
(a+c-b)/b=(a/b)+(c/b)-1
(a+b-c)/c=(a/c)+(b/c)-1
∴上面三个式子相加,可得
左边
=[(b/a)+(a/b)]+[(b/c)+(c/b)]+[(a/c)+(c/a)]-3
≥2+2+2-3=3 (基本不等式)
等号仅当a=b=c>0时取得
∴原命题成立
∵(b+c-a)/a+(a+c-b)/b+(a+b-c)/c=b/a+c/a-1+a/b+c/b-1+a/c+b/c-1=b/a+c/a+a/b+c/b+a/c+b/c-3
=(b/a+a/b)+(c/a+a/c)+(c/b+b/c)-3>=2+2+2-3=3
(b+c-a/a)+(a+c-b/b)+(a+b-c/c)=2a+2b+2c-3=2(a+b+c)-3
只能得出这个式子大于-3,不能证明大于等于3